Kajian Kondisi Lamun Pada Perairan Pantai Waemulang Kabupaten Buru Selatan - Samson, Efraim Samson; Kasale, Daniati; Wakano, Deli (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Research of seagrass vegetation structure has been carried out in Waemulang Coastal Waters, South of Buru Regency. This explorative study uses a linear quadrate transect method with 13 transect lines that are mounted perpendicular to the coastline, starting from the highest tide to the lowest tide. The results showed mixed vegetation types with species composition consisting of 5 seagrass species, namely: Enhalus ocoroides, Halophila ovalis, Thalassia hemprichii, Cymodocea serrulata and Cymodocea rotundata, which are members of 2 orders, 2 families, and 4 genera of seagrasses. The species that are most commonly found and have a value of density, relative density, frequency type, relative frequency, percentage of cover, relative closure, and index of important value which is higher, namely Enhalus acoroides, while the lowest, namely Halophila ovalis. In addition, the diversity index of seagrass species is 1,493, or belongs to medium category and the dominance index of seagrass species is 0.239, or there is no dominance of species. It can be concluded that the seagrass vegetation structure in Waemulang Coastal Waters is still relatively stable and Enhalus acoroides is the most influential seagrass species in the growing community. Environmental parameters are very supportive for seagrass growth in this area.